(untitled) (Tecno-Lógica, 2018)
The development of automated systems has been highlighted in the most diverse productive sectors, among them, the agricultural sector. These systems aim to optimize activities by increasing operational efficiency and quality of work. In this sense, the present work has the objective of evaluating a prototype developed for seed count in laboratory, using Arduino microcontroller. The prototype of the system for seed counting was built using a dosing mechanism commonly used in seeders, electric motor, Arduino Uno, light dependent resistor and light emitting diode. To test the prototype, a completely randomized design (CRD) was used in a two-factorial scheme composed of three groups defined according to the number of seeds (500, 1000 and 1500 seeds tested), three speeds of the dosing disc that allowed the distribution in 17, 21 and 32 seeds per second, with 40 repetitions evaluating the seed counting prototype performance in different speeds. The prototype of the bench counter showed a moderate variability of seed number of counted within the nine tests and a high precision in the seed count on the distribution speeds of 17 and 21 seeds per second (s-1) up to 1500 seeds tested. Therefore, based on the observed results, the developed prototype presents itself as an excellent tool for counting seeds in laboratory.